Empowering communities through waste management education: a case study of private islamic boarding school An-Nusyur in Sumenep Regency, Madura Island. - Puji Astuti, Ratna Dwi; Sulistyorini, Lilis; Arfiani, Novi Dian; H.J, Mukono; Atmaka, Dominikus Raditya; Mahmudiono, Trias; Mulia, Shinta Arta; Pratiwi, Damai Arum; Febriyanto, Eka Cahya Febriyanto; Ismail, Wan Ismahanisa; Mohamed Nor, Nik Mohd Izham (Universiti Teknologi Mara, Kedah, 2024)
Effective waste management is essential for preserving environmental sustainability and protecting public health, especially in rural areas. This study examines the implementation and outcomes of a waste management educational program at Private Islamic Boarding School An-Nusyur in Sumenep Regency, Madura Island. The initiative seeks to tackle local waste management difficulties through education and the active involvement of the community. The curriculum encompasses waste segregation, the 4R waste principles (reduce, reuse, recycle, and replace), and the ecological consequences of inappropriate trash disposal. We have a total of 38 people enrolled in our program. The pre-test average was 69.29, while the post-test average was 87.71, showing an 18.42% increase. The results demonstrate substantial enhancements in participants' understanding of trash management. Heightened consciousness and engagement in sustainable practices were noted both inside the educational institution and in the neighboring community. The initiative fostered a culture of environmental responsibility, empowering children to champion sustainable waste practices. Collaborative endeavors with local government and environmental organizations improved the program's reach and efficacy. This program showcases the capacity of educational programs to assist communities in addressing waste management challenges. Private Islamic Boarding School An- Nusyur effectively addresses both immediate environmental concerns and long-term community development and environmental protection in Sumenep Regency by incorporating trash management education into the school curriculum. The findings suggest that other rural environments can replicate similar educational initiatives to foster sustainable waste management practices and foster community engagement. Efficient waste management is crucial for the preservation of the environment and the promotion of public health, particularly in rural regions. This study investigates the implementation and effects of a waste management teaching program at Private Islamic Boarding School An-Nusyur in Sumenep Regency, Madura Island.